Contagio Bancario y Requerimiento Mínimo de Liquidez - Mejía , Kléber (2007)
This research focuses in the development of a model capable to measure the probability of contagion among Ecuadorian banks caused by liquidity runs. The model uses econometric analysis based on quantitative data as well as qualitative data, such as expert opinions, in a novel treatment for this issue. The applied methodology is also able to estimate minimal requirements of liquidity needed by the financial system in order to confront a widespread run of deposits as well as the expected time before a hypothetical “Pool de Fondos” would run out of money in front of a substantial decrease in the level of deposits kept by the system.